Affirmation of the Trade Performance between Islands as Shield of Indonesia Confront MEA - Abdi Abdi; Usman Rianse; Weka Gusmiarty Abdullah; Ine Fausayana; Ilma Sari Mustaqiyama Rianse (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
AbstractIndonesia is a maritime country with many unutilize resources but high in experiences in the world trade pass through ocean. However, in this era, the ocean and the fishery sector of Indonesia confront the new challenge called Asian Economy Society (MEA). The Policy of accelerating the Ocean and the fishery industrialization is one of the strategic step to face MEA. It must be sinergistic with the increase of the trade performance between islands. The increase of the trade performance between islands could be done by constructing new harbor through the approachment of “Tol Laut” and the change of consumer behavior. It will affect in : (1) The increase of market share in the ocean and the fishery comodity in Global Market ; (2) The Acceleration of the Ocean and the fishery industrialization ; (3) The increase of value of the ocean and the fishery comodity ; (4) The increase of The state’s income ; (5) The increase of fhiserman and fish farmer prosperity ; (6) The Defense of The Unity of the Republic of Indonesia.Key Word : MEA, trade between Islands, performance, Industrialization